2021
DOI: 10.1111/ropr.12417
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Climate Governance, Anticipatory Adaptation, and the Vulnerability‐Readiness Nexus

Abstract: Adapting to the social, economic, environmental, and health threats resulting from climate change requires successful multilevel governance and improved decision‐making processes. In this study, we evaluate explanatory relationships that support climate change adaptation. Based on the existing literature, we develop and apply a mixed‐methods approach to examine refined drivers of the vulnerability‐readiness nexus. This study examines the context of multilevel governance and the role of anticipatory adaptation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…In summary, this systematic literature review has delved deeply into the multidimensional field of climate change adaptation measures, shedding light on its evolution and current trends [34,35]. Our examination has demonstrated an intensifying trend in research output, a testament to the mounting global urgency and commitment to address climate change adaptation.…”
Section: Research Gap Identificationmentioning
confidence: 93%
“…In summary, this systematic literature review has delved deeply into the multidimensional field of climate change adaptation measures, shedding light on its evolution and current trends [34,35]. Our examination has demonstrated an intensifying trend in research output, a testament to the mounting global urgency and commitment to address climate change adaptation.…”
Section: Research Gap Identificationmentioning
confidence: 93%
“…The discussions on governance factors encompass political factors and institutional and societal frameworks that determine climate finance resource allocation and regulation. The efficacy of national and local governments, non-government institutions, and relevant international institutions in climate governance has been assessed [6,[50][51][52][53]. While examining adaptation readiness from a climate governance perspective, [23] examined the effectiveness of governance across various countries and found that it impacts climate vulnerability.…”
Section: Climate Vulnerability Adaptation Readiness and Adaptation Fi...mentioning
confidence: 99%